Novel Catalyst System for Hydrostannation of Alkynes. Issue 5 (8th January 2014) - Gupta, Sreya; Do, Youngshil; Lee, Jin Hee; Lee, Miryeong; Han, Junghoon; Rhee, Young Ho; Park, Jaiwook
Abstract A catalyst system was developed for the highly regio‐ and stereoselective hydrostannation of a range of alkynes with tributylstannane under mild conditions. The active catalytic species was generated from a stable diruthenium complex by illuminating household fluorescent light (30 W) at room temperature.